How much is enough—Can resting state fMRI provide a demarcation for neurosurgical resection in glioma?. (January 2018) - Ghinda, Diana C.; Wu, Jin-Song; Duncan, Niall W.; Northoff, Georg
Highlights: Rs-fMRI is a suitable alternative to task-based fMRI in patients who are unable to cooperate. There is considerable evidence of diffuse functional reorganization occurring in the setting of gliomas. There are local and interhemispheric functional connectivity alterations involving different networks. Rs-fMRI may yield new functional biomarkers of glioma that could improve the ability to diagnose, treat and predict patients' outcomes. Abstract: This study represents a systematic review of the insights provided by resting state functional MRI (rs-fMRI) use in the glioma population. Following PRISMA guidelines, 45 studies were included in the review and were classified in glioma-related neuronal changes (n = 28) and eloquent area localization (n = 17). Despite the heterogeneous nature of the studies, there is considerable evidence of diffuse functional reorganization occurring in the setting of gliomas with local and interhemispheric functional connectivity alterations involving different functional networks. The studies showed evidence of decreased long distance functional connectivity and increased global local efficiency occurring in the setting of gliomas. The tumour grade seems to correlate with distinct functional connectivity changes. Overall, there is a potential clinical utility of rs-fMRI for identifying the functional brain network disruptions occurring in the setting of gliomas. Further studies utilizing standardized analytical methods are required to elucidate the mechanism through which gliomas induce global changes in brain connectivity.